The Influence of Using the Beelinguapp Application on Students’ Pronunciation Mastery - Nadhila Arufah Chafshah; Dewi Kurniawati; Hasanul Misbah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study examines the effect of the Beelinguapp application on students’ pronunciation mastery in an EFL context. A quasi-experimental design was employed with two classes of eleventh-grade students at SMK Al-Huda Jati Agung. One class was assigned as the experimental group using Beelinguapp, while the other served as the control group receiving conventional instruction. Data were collected through pre-tests and post-tests and analyzed using paired sample t-tests and independent t-tests. The findings revealed that the experimental group's mean score improved from 62.71 to 81.19, with a mean difference of 18.48 (p = 0.000). In contrast, the control group's mean score increased from 61.72 to 67.19, with a smaller mean difference of 5.47 (p = 0.006). The independent t-test confirmed that the experimental group achieved significantly greater gains than the control group (p < 0.05). These results demonstrate that Beelinguapp is effective in enhancing pronunciation mastery, particularly by providing students with authentic pronunciation models, multimodal input through audio and text, and opportunities for interactive practice. The study highlights the value of integrating mobile-assisted language learning applications into classroom instruction to foster more engaging and effective pronunciation learning. It also suggests that digital tools like Beelinguapp can help overcome common challenges in pronunciation teaching, where traditional approaches often provide limited exposure and practice.